Relationships between distinct blood monocyte subsets and migrating intestinal lymph dendritic cells in vivo under steady-state conditions. - Yrlid, U; Jenkins, C; Macpherson, G (2006)
The origins of dendritic cells (DCs) are poorly understood. In inflammation, DCs can arise from blood monocytes (M(O)s), but their steady-state origin may differ, as shown for Langerhans cells. Two main subsets of M(O)s, defined by expression of different chemokine receptors, CCR2 and CX(3)CR1, have been described in mice and humans. Recent studies have identified the inflammatory function of CCR2(high)CX(3)CR1(low) M(O)s but have not defined unambiguously the origin and fate of CCR2(low)CX(3)CR1(high) cells. In this study, we show that rat M(O)s can also be divided into CCR2(high)CX(3)CR1(low)(CD43(low)) and CCR2(low)CX(3)CR1(high)(CD43(high)) subsets with distinct migratory properties in vivo. Using whole body perfusion to obtain M(O)s, including the marginating pool, we show by adoptive transfer that CD43(low) M(O)s can differentiate into CD43(high) M(O)s in blood without cell division. By adoptive transfer of blood M(O)s followed by collection of pseudoafferent lymph, we show for the first time that a small proportion of intestinal lymph DCs are derived from CCR2(low)CX(3)CR1(high)(CD43(high)) blood M(O)s in vivo under steady-state conditions. This study confirms one of the possible origins of CCR2(low)CX(3)CR1(high) blood M(O)s and indicate that they may contribute to migratory intestinal DCs in vivo in the absence of inflammatory stimuli.